Destroying Yemen what chaos in Arabia tells us about the world - Blumi, Isa (University of California Press, 2018)
Since March 2015, a Saudi-led international coalition of forces--supported by Britain and the United States--has waged devastating war in Yemen. Bringing new sources and a deep understanding to bear on Yemen's profound, unwitting imbrication in international affairs, this explosive book ultimately tells an even larger shock-doctrine story of today's political economy of global capitalism, development, and the war on terror as disparate actors intersect in Arabia.